1981
DOI: 10.1172/jci110132
|View full text |Cite
|
Sign up to set email alerts
|

The developmental changes in plasma adrenal androgens during infancy and adrenarche are associated with changing activities of adrenal microsomal 17-hydroxylase and 17,20-desmolase.

Abstract: A B S T R A C T The plasma concentrations of dehydroepiandrosterone, androstenedione, and dehydroepiandrosterone sulfate decrease during the first year of life, remain low during childhood, and then increase during adrenarche. To determine whether alterations in adrenal enzyme activity might explain the changing secretory pattem of the adrenal androgens, we measured human adrenal microsomal 3,8-hydroxysteroid dehydrogenase-isomerase, 17,20-desmolase, 17-hydroxylase, and 21-hydroxylase activities. 12 adrenals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(38 citation statements)
references
References 31 publications
(34 reference statements)
0
37
0
1
Order By: Relevance
“…Consequently, in the physiological situation, almost all androgen synthesis proceeds through DHEA, which, therefore, is considered the principal human androgen precursor. An early study employing human adrenal microsomes from individuals of different ages found lower CYP17A1 activities in individuals aged 2 months to 9 years than in adults (131) and subsequently has been cited as evidence for a characteristic increase in 17,20 lyase activity at the time of adrenarche. However, current in vivo evidence points towards a much earlier onset of adrenal androgen secretion at around age 3 years (17).…”
Section: Adrenal Steroidogenesis During Adrenarchementioning
confidence: 99%
“…Consequently, in the physiological situation, almost all androgen synthesis proceeds through DHEA, which, therefore, is considered the principal human androgen precursor. An early study employing human adrenal microsomes from individuals of different ages found lower CYP17A1 activities in individuals aged 2 months to 9 years than in adults (131) and subsequently has been cited as evidence for a characteristic increase in 17,20 lyase activity at the time of adrenarche. However, current in vivo evidence points towards a much earlier onset of adrenal androgen secretion at around age 3 years (17).…”
Section: Adrenal Steroidogenesis During Adrenarchementioning
confidence: 99%
“…Recently, the expression patterns of the steroid-metabolizing enzymes within the human fetal, neonatal and adult adrenal have been studied, giving some insight into adrenal androgen production. Of the two enzymes needed for DHEA synthesis, CYP11A (cholesterol sidechain cleavage) and CYP17 (17 -hydroxylase, 17,20-lyase), only the 17,20 lyase activity of CYP17 appears to alter its activity as the adrenal initiates DHEA production at adrenarche (Schiebinger et al 1981, Suzuki et al 2000. There also appears to be a negative correlation between the enzyme type II 3 -hydroxysteroid dehydrogenase (HSD3B2) and DHEA(S) production (Doody et al 1990, Endoh et al 1996, Gell et al 1998a, Suzuki et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested that the increase in adrenal androgen production at adrenarche is due to some maturational change within the adrenal gland itself (11)(12)(13). It has been reported that the zona reticularis, the innermost zone of the adrenal cortex that predominantly secretes adrenal androgens, appears at the time of adrenarche (11).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that maturational changes in the activities of some adrenal enzymes (17-hydroxylase, 17-20-lyase and the 3b-hydroxysteroid dehydrogenase, D 4-5 isomerase system) may account for alterations in steroidogenesis favouring androgens (13)(14)(15). Alternatively, factors extrinsic to the adrenal may specifically control adrenal androgen biosynthesis and secretionfor example, the putative cortical androgen stimulating hormone.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation